USABILITY-BASED MEDICAL INFORMATION SYSTEM PROTOTYPE USES A GOAL-DIRECTED DESIGN TO IMPROVE PATIENT ACCESS TO HOSPITAL SERVICES - Anjik Sukmaaji; Sri Hariani Eko Wulandari; Dimas Fitrah Maulana (International Research of Multidisciplinary Analysis, 2023)
The results of preliminary research on the use of a medical website of a  hospital showed a usability value of 2.3 out of a scale of 4, which means that the quality of the website's services is not satisfactory, so patients are reluctant to   use medical  portal  services.   Even though the  hospital  patient service portal  is an essential medium  after the Covid-19  pandemic, it can be  used to  increase pasiesn access to  hospitals  by not knowing the time.  The   non-stop  operation  of the portal can help patients  get the information and  services that  patients need  anytime and anywhere.   .  However, not all services can satisfy customers or patients.  The behavior of the  people of the "New Normal" era  who must still pay attention to  distance, and changes in consumer behavior who are always looking for convenience through the internet, cause  hospitals to  be able to manage  portals which can meet the needs of hospital consumers.  Unfortunately, medical information portals are still managed with no regard for patient information needs.  The biggest challenge  in this study is achieving the hospital's goal of providing superior services for patients  by paying attention to medical  information needs.  patients. Therefore  ,     this research seeks to improve website  services  by  redesigning  the website as a prototype using  The design approach  of a  prototype Goal Directed Design (GDD) of a website can be known for its usability value. The end  of the study  showed that the  increase in the usability test results was based on the average value of all usability factors of 3.69 from the  original condition of  2.3 or an increase in the usability value of 60%.